ARE CONSULTING AND AUDITING COMPATIBLE?–A CONTRARY VIEW. - Hylton, Delmer P. (The Accounting Review, 1964)
Abstract The article informs that in the April, 1963 issue of the "Journal of Accountancy," Kenneth S. Axelson' expresses the opinion that management services do not compromise an independent certified public accountant's necessary independence. This article takes a contrary view, one which certainly will not be popular either with the American Institute (which strongly promoted management services from the CPA) or with the many firms which are now engaged in these services. Nevertheless, the issue is not settled, as Axelson's article would have been pointless had this been the case. The case for management services. By-passing the question of the competence of the CPA, the basic premise of those supporting combined audit and management services from the same accounting firm for the same client is that the auditor only recommends, that he does not and cannot make the final decision as to implementing the recommendation. Thus, management of the client's affairs is still in the client's control and therefore the auditor, in a subsequent audit is not in effect auditing his own work. From this reasoning it is then concluded that the auditor's independence is not impaired by rendering management services to an audit client.